2016
DOI: 10.1016/j.addr.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan as a therapeutic target in human diseases

Abstract: Accumulation and turnover of extracellular matrix is a hallmark of tissue injury, repair and remodeling in human diseases. Hyaluronan is a major component of the extracellular matrix and plays an important role in regulating tissue injury and repair, and controlling disease outcomes. The function of hyaluronan depends on its size, location, and interactions with binding partners. While fragmented hyaluronan stimulates the expression of an array of genes by a variety of cell types regulating inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 325 publications
(377 reference statements)
4
117
0
6
Order By: Relevance
“…1). In earlier studies, considerably elevated serum HA values have been observed in AML [26], multiple myeloma [29], malignant lymphoma [30], myelofibrosis, and CML [31], and also in various nonhematological diseases [13]. These studies confirmed that elevated serum HA levels may accompany malignant diseases.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…1). In earlier studies, considerably elevated serum HA values have been observed in AML [26], multiple myeloma [29], malignant lymphoma [30], myelofibrosis, and CML [31], and also in various nonhematological diseases [13]. These studies confirmed that elevated serum HA levels may accompany malignant diseases.…”
Section: Discussionsupporting
confidence: 72%
“…It has also been detected in the bone marrow matrix, as an essential component [2]. Several studies have reported that HA levels are increased in a variety of human diseases [13] such as liver fibrosis and cirrhosis [14], diabetes [15,16], heart diseases [15], and lung fibrosis [13]. The role of HA in several malignancies such as breast cancer [17,18] and malignant pleural mesothelioma [19], has already been extensively investigated [3,6,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The CD44-HA ligand-receptor pair is well known for its active tumor-targeting efficacy in cancer therapy. 14,[20][21][22][23] The targeting delivery systems such as nanoparticles, polymeric micelles, liposomes, emulsions, and nanogels with HA provide several advantages as drug carriers in both active and passive targeting of tumor receptors for drug delivery. 8,10,24,25 However, there are still several limitations, including low tumor-targeting efficacy, low bioavailability, undesirable tissue distribution, low drug loading dose, the need for relatively large injection volumes, low antitumor efficacy, unpredictable toxicity, and an initial drug release burst.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies (their size is about 12 nm) endowed with fluorescent dyes (e.g., Alexa Fluor 488 λEm=525 nm and Texas Red λEm=609 nm) [15][16][17] were used in the development of a wide range of effective targeted therapies [18][19][20][21][22] but they create clustering artifacts due to limited antibody penetration, which have an impact on insufficient labeling density. Thus, ligands that have been exploited for chemotherapeutic agent targeting systems can include monoclonal antibodies [23][24][25][26][27][28] but also low molecular weight receptor-binding conjugates such as dyelabeled peptides (arginine-glycine-aspartic acid-Cyt5,5) [29], peptide hormones [30,31], receptor antagonist and agonists [32], aptamers [33][34][35], transferrin [36][37], oligosaccharides [38], glycoconiugates [39], polyunsaturated fatty acids [40], oligopeptides [41,42], vitamin B12 [43], folic acid [44][45][46][47][48][49][50][51][52][53][54] and hyaluronic acid [55,56]. These ligands can be regarded as a tumor-specific receptor to construct a "guided molecular ...…”
Section: Fluorescent Small Molecules As Cell-type-specific Imaging Prmentioning
confidence: 99%